IMF-Supported Programs : Recent Staff Research - Rebucci, Alessandro (International Monetary Fund, 2006)
Research work by the IMF's staff on the effectiveness of the country programs the organization supports, which has long been carried out, has intensified in recent years. IMF analysts have sought to 'open up the black box' by more closely examining program design and implementation, as well as how these influence programs' effectiveness. Their efforts have also focused on identifying the lending, signaling, and monitoring features of the IMF that may affect member countries' economic performance. This book reports on a large portion of both the new and the continuing research. It concludes that IMF programs work best where domestic politics and institutions permit the timely implementation of the necessary measures and when a country is vulnerable to, but not yet in, a crisis. It points to the need for a wider recognition of the substantial diversity among IMF member countries and for programs to be tailored accordingly while broadly maintaining the IMF's general principle of uniformity of treatment.